Dyslexia is my gift a campaign to raise awareness, to educate, and to promote the many gifts of dyslexia for children ages 8-12 old and their parents - Salanga, Miguel Carlos A.; Tañedo, Jose Alberto (Quezon City College of Fine Arts, University of the Philippines Diliman, 2019)
Dyslexia is a specific learning disability which is neurobiological in origin. It is a difference with how the brain is wired which results to people who have the condition to experience difficulties when it comes to reading, writing and spelling. Dyslexia is an invisible disability that's not as easily noticeable to the naked eye as compared to a physical disability. This leads to people who don't have an in depth understanding of the condition to mistake people with dyslexia for being stupid, lazy, or incapable individuals. The problem mostly persists in the early years of a child's academic life. Once the dyslexic child reaches a higher level of education, readings starts to become more complex and symptoms start to persist more noticeably. A child with dyslexia already experiences difficulty with his/her academics and to add to that, he/she may also experience bullying from their peers who are misinformed. This results to the child with dyslexia to lose his/her self-confidence and start to feel insecure of their abilities which endangers their wellbeing and hinders the development of their full potential. "Dyslexia is my Gift" is a campaign that aims to raise awareness about dyslexia and correct the misconceptions that the public correctly believe towards the condition. Dyslexia doesn't have to be seen as something that is negative. Everyone has strengths and weaknesses and this campaigns aims to help the public see the gift behind dyslexia and develop positive attitudes towards the condition.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography : leaves 109-111.
Keywords: Dyslexia; Dyslexic children; Dyslexics